2021
DOI: 10.1021/acs.est.1c01932
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rates of Transition-Metal-Ion-Catalyzed Oxidation of S(IV) in Aqueous Aerosols: Insights into Sulfate Aerosol Formation in the Atmosphere

Abstract: The oxidation of S­(IV) is a critical step in the fate of sulfur dioxide emissions that determines the amount of sulfate aerosol in the atmosphere. Herein, we measured accelerated S­(IV) oxidation rates in micron-sized aqueous aerosols compared to bulk solutions. We have investigated both buffered and unbuffered systems across a range of pH values in the presence of atmospherically relevant transition-metal ions and salts and consistently found the oxidation rate to be accelerated by ca. 1–2 orders of magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 54 publications
(140 reference statements)
1
73
0
Order By: Relevance
“…Similarly, the spontaneous oxidation induced by the water radical cation has several implications for atmospheric and aerosol chemistry, topics that involve sub-micrometer size droplets (e.g., spray and organic aerosols) ( Gantt and Meskhidze, 2013 ; Ault and Axson, 2017 ; Kirpes et al, 2018 ). Although an enhanced rate of oxidation has been reported in aerosols via other mechanisms and other reactive species (e.g., oxygen, ozone, hydroxyl radicals or hydrogen peroxide) ( Glasius et al, 2000 ; Richards-Henderson et al, 2016 ; Liu et al, 2020 ; Angle et al, 2021 ), we suggest that the possible role of the water radical cation chemistry is worthy of attention. The effects of this radical species might be significant considering the generality here demonstrated for X=Y containing compounds (common moieties in VOCs).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, the spontaneous oxidation induced by the water radical cation has several implications for atmospheric and aerosol chemistry, topics that involve sub-micrometer size droplets (e.g., spray and organic aerosols) ( Gantt and Meskhidze, 2013 ; Ault and Axson, 2017 ; Kirpes et al, 2018 ). Although an enhanced rate of oxidation has been reported in aerosols via other mechanisms and other reactive species (e.g., oxygen, ozone, hydroxyl radicals or hydrogen peroxide) ( Glasius et al, 2000 ; Richards-Henderson et al, 2016 ; Liu et al, 2020 ; Angle et al, 2021 ), we suggest that the possible role of the water radical cation chemistry is worthy of attention. The effects of this radical species might be significant considering the generality here demonstrated for X=Y containing compounds (common moieties in VOCs).…”
Section: Discussionmentioning
confidence: 59%
“…The mechanisms of heterogeneous SO 2 oxidation in aerosols, however, remain a matter of considerable debate. , Cheng et al explained the missing sulfate source with oxidation of SO 2 by NO 2 in aerosol water, which can occur rapidly within a 5.4 < pH < 6.2 range . Hung et al identified that the SO 2 oxidation by O 2 can occur via an uncatalyzed route at the surface of acidic aerosol droplets. , Liu et al found that the aqueous SO 2 oxidation by H 2 O 2 can be accelerated 50-fold by the salt effects in aerosol microdroplets .…”
Section: Introductionmentioning
confidence: 99%
“…This enhanced reaction rate is independent of aerosol acidity and was regarded as a major contributor to the missing sulfate . Angle et al observed that the aqueous TMI-catalyzed oxidation of S­(IV) by O 2 was faster in the optically levitated aerosol droplets than in the bulk solution, although the TMI-catalyzed reaction is unfavorable at the high-ionic-strength condition . Wang et al reported that the Mn­(II)-catalyzed oxidation of SO 2 by O 2 at aerosol surface was 2 orders of magnitude faster than the other known reaction mechanisms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The pH at surfaces of aerosols can also be different from those in aerosol bulks, 40 and a recent aerosol kinetics study observed the enhanced rates of catalyzed oxidations in aerosols and attributed this enhancement to the pH gradient at the air-water interfaces of aerosols. 41 In the present work, we choose the oxidation reaction of sodium thiosulfate (STS), Na 2 S 2 O 3 , with O 3 as a model system of sulfur oxidation in aerosols, as such model reaction has been utilized in several studies associated with atmospheric aerosol chemistry. [42][43][44] In particular, the present work exploited aerosol optical tweezers (AOT) combined with Ra-…”
Section: Introductionmentioning
confidence: 99%